2006
DOI: 10.3386/w12746
|View full text |Cite
|
Sign up to set email alerts
|

How Large Is the Housing Wealth Effect? A New Approach

Abstract: This paper presents a simple new method for estimating the size of 'wealth effects' on aggregate consumption. The method exploits the well-documented sluggishness of consumption growth (often interpreted as 'habits' in the asset pricing literature) to distinguish between short-run and long-run wealth effects. In U.S. data, we estimate that the immediate (next-quarter) marginal propensity to consume from a $1 change in housing wealth is about 2 cents, with a final long-run effect around 9 cents. Consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(131 citation statements)
references
References 30 publications
5
125
0
1
Order By: Relevance
“…In other studies, stock market wealth shows the larger impact (Dvornak andKohler, 2003 andDe Veir-man andDunstan, 2008). Ludwig and Slok (2004) and Carroll, Otsuka and Slacalek (2006) have emphasized that the long-run responsiveness of consumption to permanent changes in wealth depends on the institutional framework. In particular, the wealth effect is higher for countries with a market-based than for countries with a bank-based financial system.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, stock market wealth shows the larger impact (Dvornak andKohler, 2003 andDe Veir-man andDunstan, 2008). Ludwig and Slok (2004) and Carroll, Otsuka and Slacalek (2006) have emphasized that the long-run responsiveness of consumption to permanent changes in wealth depends on the institutional framework. In particular, the wealth effect is higher for countries with a market-based than for countries with a bank-based financial system.…”
Section: Introductionmentioning
confidence: 99%
“…The problem with the cointegration method is that it implicitly requires the existence of a stable long term relationship between consumption, income and wealth. However, in our sample of 50 years, there have been major changes in the structure of the economy due to changes in tax structure, demographics, productivity growth, financial structure, social insurance, and many other aspects of the economy (Carroll et al, 2006). Therefore, as Carroll et al (2006) noted, trying to find the existence of a cointegrating relationship which satisfies the condition of stability is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our sample of 50 years, there have been major changes in the structure of the economy due to changes in tax structure, demographics, productivity growth, financial structure, social insurance, and many other aspects of the economy (Carroll et al, 2006). Therefore, as Carroll et al (2006) noted, trying to find the existence of a cointegrating relationship which satisfies the condition of stability is problematic. They criticized the idea long-run relationship and estimated the marginal propensity to consume (MPC) out of wealth with alternative methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Almeida et al (2006) have reported evidence that the sensitivity of house prices and mortgage borrowings to income shocks is higher in countries with higher loan-to-value ratios. Ludwig and Sløk (2004) and Carroll et al (2006) have emphasized that the long-run responsiveness of consumption to permanent changes in housing wealth is higher for countries with a market-based than for countries with a bank-based financial system. According to Catte et al (2004), strong impacts of real house prices on consumption can be detected especially in countries that have large, efficient and responsive mortgage markets.…”
Section: Introductionmentioning
confidence: 99%